Amphiphilic starch with 3-(trimethylammonium chloride)-2-hydroxypropyl and octenylsuccinyl substituents for strong adhesion to fibers. Issue 6 (19th March 2018) - Xu, Zhenzhen; Zhu, Zhifeng; Li, Wei; Zhang, Chaohui
Abstract: Amphiphilic starch derivatives with oleophilic octenylsuccinyl (OS) and hydrophilic 3-(trimethylammonium chloride)-2-hydroxypropyl (TMACHP) substituents were derived by the quaternization of acid-treated maize starch with N -(3-chloro-2-hydroxypropyl) trimethylammonium chloride followed by the octenylsuccinylation with octenylsuccinic anhydride. Two series of amphiphilic starches with differential degrees of substitution ( DS ) and mole percentages of OS to the total substituents introduced onto the starch were characterized by elemental analysis, chemical titration, and FTIR spectroscopy. The effects of the DS and mole percentage on the adhesion of the starch to fibers were investigated using a legal method (FZ/T 15001-2008). The modification was able to significantly improve the adhesion of starch to cotton and polyester fibers due to the reduced surface tension of the cooked starch paste. The adhesion depended not only on the DS of OS and TMACHP substituents, but also on the mole percentage of the OS. The amphiphilic starch had superior adhesion to acid-treated and TMACHP-functionalized starches. The adhesion of the amphiphilic starch was found to reach its maximum at a mole percentage of 70.6% OS. An increase in the total DS reduced the surface tension and favored adhesion, but disfavored reaction efficiency. Based on the adhesion and reaction efficiencies, the amphiphilic starch with a total DS in the range of 0.029–0.051 and a mole percentage of 70.6% OS showed potential for use in warp sizing.